Measurement of Economic Risk for a Non-Probabilistic Problem Formulation - Kotsyuba Oleksiy S. (Research Centre of Industrial Problems of Development of NAS of Ukraine, 2021)
The subject of the article is the methodical apparatus for quantitative assessment of the degree of economic risk for the situation of decision-making, under load of the nonstochastic (nonprobabilistic) uncertainty. The research implemented the task of further development of fuzzy-multiple risk measurement instrumentarium for the case of simultaneous nonstochastic uncertainty of assessments of the criterial economic indicator (criterion) and its norm. In accordance with the set goal and methodical approach to the interpretation of fuzzy assessments on the basis of an analogy between random and fuzzy values in the work a number of practically significant situations determined by the nature of the nonstochastic assessments of the criterial economic indicator and its norm were consistently considered, for each of these mathematical ratios were found to calculate the degree of risk. The proposed calculation formulas were tested on conventional examples. The results of the tests showed the capability of the developed computing apparatus. The research also focuses on the situation of risk measurement, when the assessment of the criterial economic indicator is modeled as a random variable, while its normative level is described by an assessment, either interval or fuzzy. As a perspective direction of further scientific research on the issues raised in the article, the formation of some generalized methodology for quantitative assessment of the degree of economic risk, which would allow to measure the risk for various situations of information uncertainty from a single theoretical position, is defined.